Perbaikan Proses Produksi dan Pemasaran Melalui Penerapan Mesin Produksi, Pembuatan Label Kemasan, Materi dan Media Promosi Digital untuk Kelompok Masyarakat Nenas Berduri (PONARI) - Wahyuni, Retno Tri; Susianti, Elva; Sari, Rika Perdana (LPPM UMRI, 2022)
The Pineapple Community Group (PONARI) is one of those recommended by the Kampar Integrated Business Service Center (PLUT) to provide assistance. The Covid-19 pandemic condition affected PONARI's business, where Pokmas experienced a drastic decrease in income. The occurrence of the pandemic caused many government agency activities or events, wedding parties, which usually place orders for pineapple processed products, to not be carried out. Marketing efforts to other places such as entrusting them to gift shops are very limited because the processed products do not yet have a PIRT permit, even though the demand from gift shops is actually quite a lot. Thus, there is a need for assistance for PONARI so that they can rise from adversity due to the pandemic. The form of assistance for PONARI carried out in this community service program is the application of production machines, improvement of packaging labels, promotional materials and media. The results of community service activities are in the form of two production machines that have been implemented and have a positive impact on the production process. Other results are in the form of more modern and attractive packaging labels, promotional materials with attractive taglines and promotional media to support digital marketing.